Social Organization Participation on Inhabitable House Rehabilitation - Setyo Sumarno (Jurnal Penelitian Kesejahteraan Sosial, 2016)
House is one the basic of need, as a place of rest and refuge from a variety of situations and threats. House is as well as a medium for the creation of social interaction, cultural tranfer, implementattion of family education, and evenbecomes a status symbol. For the moyority of people considered a poor family, house is just as a given regardless of its feasibility in terms of physical, mental and social. Jam’iyyah foundation ar Rahmah Kuwait, one of social organizationhelped Indonesian government in overcoming poverty through ininhabitable home repairement. Aid amounting to Rp 650 million for 65 housing units concentrated in rural districts Sidorejo, Bandongan, Magelang Regency, Central Java Province. Activities came out with the involvement of cadres of disaster preparedness, youth, social workers (PSM), social workers districts (TKSK) and scouts. Community participation were in the form of money, goods, energy, and mind. This success can not be separated from the role of village offials; community leaders, who facilitated for formation of the committee and mobilize communities to work together; Camat (district leader) role in facilitating the proposal; and local goverment in funding home improvements and refining. Home improvement which was originally planned only for impermanent purpose, became permanent new home with tiled floors and walls.